miR-155 and miR-122 Expression of Spermatozoa in Obese Subjects - López, Paulina; Castro, Andrea; Flórez, Martha; Miranda, Karen; Aranda, Pilar; Sánchez-González, Cristina; Llopis, Juan; Arredondo, Miguel (Frontiers in Genetics, 2018)
Obesity is characterized by mild chronic inflammation that linked with impaired iron homeostasis. Studies in human and murine show that there is a transgenerational epigenetic inheritance via the gametes in obesity, however, there is little information on changes in the expression of microRNAs related to inflammation and iron homeostasis in spermatozoa from obese subjects. The present study investigated the expression of microRNAs related to inflammation (miR-21 y miR-155) and iron nutrition (miR-122 and miR-200b) in plasma, peripheral blood mononuclear cells (PBMC) and spermatozoa from normozoospermic controls (Cn; n=17; BMI: 24,6±2,0) and obese (Ob; n=17; BMI: 32,6±4,4) men. To determine the inflammation levels we measured IL-6, TNFα and monocyte chemoattractant protein-1 (MCP1) by Magnetic Luminex® Assay. mRNA expression of IL6, TNFα and hepcidin (HAMP) in PBMC were evaluated by RT-qPCR. The analysis of microRNAs were performed using the Taqman® assays. The iron content in PBMC, seminal plasma and spermatozoa was determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). High serum IL6, TNFα and MCP1 levels were observed in Ob group (p<0.05). Gene expression analysis shown an increased abundance relative of TNFα (p=0.018), HAMP (p=0.03) and IL6 (p=0.02) in PBMC from obese subjects. Also, we observed high levels of serum ferritin (p=0.03), iron content in seminal plasma (p=0.04) and spermatozoa (p=0.002), but lower serum Fe (p=0.007) in obese subjects. In the Ob group a high expression of miR-155 (p=0.02) and miR-21 (p=0.03) was observed in PBMC and miR-122 (p=0.03) in plasma. In sperm, both miR-155 (p=0.004) and miR-122 (p=0.028) were high in the Ob group. Our results showed that obese subjects have increased expressions of miR-155 and miR-122, two microRNAs that were previously related with inflammation and iron metabolism, respectively, at both the systemic and sperm levels.